Peran Pemerintah Dalam Pengelolaan Pariwisata Kebun Raya Massenrempulu Kabupaten Enrekang - Riska, Riska; Muhammadiah, Muhammadiah; Sudarmi, Sudarmi (Universitas Muhammadiyah Makassar, 2020)
This study purposed to find out the role of government in tourism management. As well as what factors were facing the government in the management of Massenrempulu Botanical Gardens Tourism in Enrekang Regency. This study used qualitative research methods. The data collection techniques used observation, interviews and documentation. The results of this study showed that the role of the government (Department of the Environment) in the management of the tourism sector, especially the Botanical Gardens of Massenrempulu, Enrekang Regency was very important. There were several roles of the government in the management of Massenrempulu Botanical Gardens in Enrekang Regency, namely the government's role as a regulator, facilitator and motivator. Factors that influenced the development of attractions were supporting factors, namely motivators and regulators, while inhibiting factors were the lack of water retention, and limited funds.